The history of televisión news in Colombia and the construction of a critical memory of society and journalism 1954-1984 - López de la Roche, Fabio (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
The paper explores some of the social and cultural processes which acccompanied the birth and expansion of the new medium "television" from 1954 to 1984: internationalization, Americanization,nation building.Given the lack of moderm television history in Colombian historiography ( not anecdotal or not focused exclusively on the " great men" or "pioneers" of the media or the TV industry),the absebce of television histories written from the conceptual and methodological apparatus of the moderm social sciences, this article attempts to partially fill that gap with an interpretative proposal between a history of television news genre. The two-party (Liberal-Conservative) monopoly of television information, government and centralism "bogotanizante" (Bogota-related) of TV news( accordind to the critical analysis of Luis Carlos Galan in the mid-70s) appears as the counterpart story of the parity regime and of the liberal-conservative monopoly of institutions, main characteristics of the political system of the "Frente Nacional" (1958-1974). Some cultural and political transformations that have emerged from the television information practices and from journalism itself,related to a greater openness to regional information and with some political-informative openess in the midst of the peace talks of president Belisario Betancur (1982-1986) with the M-19, are also explored in this paper.